Foam replicated porous 316l stainless steel based on taguchi method for biomedical applications - Mat Noor, Fazimah (2018)
The mismatch between elastic modulus of metal implants and bones which is also known as stress shielding, remains an unresolved issue. Porous metals are one of the most effective ways of reducing stiffness mismatches and achieving stable longterm fixation via full bone in-growth. In this work, porous SS316L is produced using